Exploring the association between statins use or HMG-CoA reductase inhibition and migraine: a systematic review and meta-analysis - Hamdy A. Makhlouf; Amr K. Hassan; Nereen A. Almosilhy; Ahmed S.A. Osman; Shrouk Ramadan; Moaz Elsayed Abouelmagd (The Journal of Headache and Pain)
Abstract Background Statins or 3‑hydroxy‑3‑methyl‑glutarylcoenzyme A (HMG‑CoA) reductase inhibitors are medications that act by reducing the cholesterol content of liver cells Moreover, statins have been found to improve endothelial function and reduce vascular wall inflammation. A growing body of research suggests that statins are associated with less risk of migraine, and they can be used to treat symptoms. However, the evidence has been inconclusive, so we aim to investigate the nature and strength of the effect of statins on the prevention and prophylaxis of migraines. Methods We conducted a comprehensive systematic search across multiple electronic databases, including PubMed, Scopus, Web of Science, and the Cochrane Library, from inception until October 2024, to include studies on the association between statins use and migraine. The outcomes of interest involved the association of the HMG-CoA reductase gene with the risk of migraine, as well as the association and efficacy of statins in migraine patients. Results Thirteen studies were included in our systematic review. Mendelian Randomization (MR) studies revealed that expression of HMGCR was associated with an increased risk of migraine with odds ratio (OR) ranging from 1.38 to 1.55 (P < 0.001). Three observational studies investigating the relationship between statins and migraine risk demonstrated a protective effect, with odds ratios ranging from 0.73 to 0.94 (P < 0.001). The findings suggest a significant reduction in overall migraine risk, particularly for migraines with aura and in patients with higher vitamin D levels. Meta-analysis of randomized controlled trials (RCTs) showed that statins significantly reduced monthly migraine frequency (MD= -3.16, 95%CI= [-5.79, -0.53]; p = 0.02, I2 = 79%; P = 0.03). RCTs supported the efficacy of statins in reducing migraine frequency, days, and intensity compared to placebo. Conclusions Statins, already well-established for cardiovascular benefits, emerge as a promising dual-purpose therapy for many neurological disorders. The association between the HMGCR gene and increased migraine risk, coupled with the possible efficacy of statins in reducing migraine frequency, may open new avenues for migraine prophylaxis. However, the variability in study design hinders definitive conclusions, so larger studies with longer follow-ups are required to ascertain both findings.